The comfort ability program for adolescents with sickle cell pain: Evaluating feasibility and acceptability of an inpatient group‐based clinical implementation. Issue 6 (19th March 2021) - Sil, Soumitri; Lee, Jennifer L.; Klosky, James; Vaz, Angela; Mee, Laura; Cochran, Shavontia; Thompson, Beth; Coakley, Rachael
Abstract: Background: Integration of nonpharmacological therapies, such as cognitive and behavioral pain management strategies, is recommended to support comprehensive disease and pain management among children and adolescents with sickle cell disease (SCD). The Comfort Ability Program for Sickle Cell Pain (CAP for SCP) introduces psychological and biobehavioral pain management strategies to children and adolescents with SCD. This study aimed to pilot the implementation of the CAP for SCP in a group setting to children and adolescents hospitalized for SCD pain examining feasibility, acceptability, and preliminary effectiveness on improving pain knowledge and coping efficacy. Method: Adaptation of CAP for SCP into a three‐session group format was guided by four phases of the Dynamic Adaptation Process model: Exploration, Preparation, Implementation, and Sustainment. Youth with SCD ( n = 57) hospitalized for pain participated in at least one session and completed self‐report of knowledge of pain management skills, pain coping efficacy, and treatment acceptance. Completion rates of sessions and qualitative feedback were gathered to evaluate feasibility and acceptability. Results: Feasibility of conducting inpatient group sessions was suboptimal; however, patients and medical providers reported moderate to high levels of treatment acceptance. Patients also reported significant improvements in knowledge of pain management skills following session 1. Conclusions: CAP for SCP is a patient‐centered first‐line psychoeducational intervention that can be integrated into clinical practice settings to introduce youth to cognitive and behavioral pain management strategies to support SCD pain management.